Sick(te) en: disease, memory and identity in the juvenile narratives Treze anos de Branca (1994) e O tempo das surpresas (2007) - Barbosa Carrijo, Silvana Augusta [UNESP]; Cardoso Tapias Ceccantini, Joao Luis [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2016)
This paper is composed by analysis of nearness and differences of the thematic features and formal procedures written of the youthful narratives Trece anos de Branca, by the Galician writer Agustin Fernandez Paz, and O tempo das surpresas, by the Brazilian writer Caio Riter. The teenagers protagonists of these narratives, affected for serious diseases, begin a plunge in their own subjectivity, through the recollection of a past that, considered in the light of the present circumstances, evinces the convertible quality of their respectives identities. Both works, representative of the esthetic quality of juvenile literary subsystem, highlight the dialogue between Literature and Medicine.
Keywords: fiction for youngsters; diseases; memory; identity